Rediscovering The Human-Headed Winged Bulls Of Khorsabad: Some New Observations - Couturaud, Barbara (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2026)
The rediscovery of a winged human-headed bull in one of the city gates of Khorsabad, ancient Dur Sharrukin, in 2023, provided an opportunity to re-examine these monumental sculptures, the jewels of the architectural decoration of the Assyrian capitals of the 1st millennium. In particular, it allowed the re-examination of their archaeological context and iconography in the light of some complex archaeological documentation dating mainly from the 19th century.1 This re-examination, made possible by the rediscovery, has highlighted some relatively unknown characteristics of these sculptures, which, surprisingly, have rarely been studied in depth or from a comparative perspective. Indeed, although these sculptures have been reproduced thousands of times since their discovery, although they accompanied the discovery of ancient Near Eastern societies in Europe through the opening of the Assyrian Museum in Paris in 1847, the first museum dedicated to the ancient Near East, and although they still make a strong impression on visitors in the few museums where they are exhibited, it is surprising to see how few publications have really looked closely at these sculptures in their archaeological context.2 Similarly, despite the admiration felt by the first excavators of Khorsabad, it is surprising, when rereading the monographs they published upon their return from the excavations, to see that these bulls are described only briefly: Paul Émile Botta shows instead a real obsession with describing the decorations on the bas-reliefs and the inscriptions,3 and Victor Place seeks at all costs to establish a complete plan of the palace.4 And so, these sculptures, measuring over 3 metres high and weighing around 30 tons, were somewhat relegated to a lower level of interest, despite – or perhaps because of? – their enormity.